Observations on the herbivore diversity in a managed tea plantation and population dynamics of major insect pest in tea with regional weather - Parthiban, M.; Rahman, Sahidur; Altaf, Nilofar; Chetia, Gouranga (Journal of Plantation Crops, 2022)
Globally, the pattern of incidence of insect pest complex has been changing in all agroecosystem due to climate change and variability. It is essential to know the incidence pattern of insect pest complex in tea for adopting successful management practice. An investigation was carried out to know the present incidence pest scenario of tea at Assam during March 2019 to Feb 2020. The results show the presence of four mite species belonging to single order and 4 families, and a total of 33 insect species belonging to 7 orders and 27 families. Among them red spider mite, tea mosquito bug, whitefly, leafhopper complex and thrips were recorded as important sucking pests. Leaf roller, tea tortrix, and flush worm were recorded as significant chewing pests. Observation shows that the tea whitefly, leaf hopper, thrips, leaf roller and flush worm has become a serious threat to the tea cultivation. The population dynamics of red spider mite and tea mosquito bug recorded a maximum incidence of 30.27 mites/ leaf and 27.17 infested flush/ bush respectively, during the month of November. Both insects were negatively regulated by maximum temperature and rainfall however relative humidity positively influenced population dynamics, as revealed by the correlation coeﬃcient. This study paves way for the development of a new plant protection module to manage the emerging insect pests in tea plantation.